2022
DOI: 10.1002/bse.3279
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corporate governance on corporate environmental sustainability: A multilevel review and research agenda

Abstract: Climate change is a major challenge facing society. Given its intricate links with business, governance scholars have shown an increasing interest in understanding how corporate governance (CG) actors can improve corporate environmental sustainability (CES). In this article, we review the literature focusing on CG and CES. We assess the importance of the motivations, expertise, and power of CG actors at different levels (individual, team, firm, and supra‐firm) for CES. Using this as a guiding framework, we bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 234 publications
0
2
0
Order By: Relevance
“…Specifically, we show that CEOs high in future focus interpret water scarcity as an opportunity, while CEOs high in past or present focus share the opposite interpretation. We hope, our study encourages future researchers to shed further light on the relationship between CEO characteristics and environmental value creation (for an overview of our knowledge in this research field, see also Karn et al, 2022).…”
Section: Discussionmentioning
confidence: 86%
“…Specifically, we show that CEOs high in future focus interpret water scarcity as an opportunity, while CEOs high in past or present focus share the opposite interpretation. We hope, our study encourages future researchers to shed further light on the relationship between CEO characteristics and environmental value creation (for an overview of our knowledge in this research field, see also Karn et al, 2022).…”
Section: Discussionmentioning
confidence: 86%
“…Specifically, we find empirical support for the notion that firms weigh environmental communication and operational practices differently depending on the type of legitimacy they are aiming to achieve. In so doing, we broaden our current understanding of board structure and its impact on environmental outcomes (Enciso‐Alfaro & García‐Sánchez, 2022; Karn et al, 2022), drawing attention to the role of legitimacy seeking strategy adopted. Moreover, we highlight the need to recognize the heterogeneous effects of different board types, which have instead been largely referred to as “good” or “bad” boards.…”
Section: Discussionmentioning
confidence: 99%
“…Friedrich et al (2022) indicated rapid increases in climate‐relevant risks and opportunities across the board. Karn et al (2022) proposed that managers should examine the latest facts about long‐term monetary benefits associated with corporate environmental sustainability; they may then be able to control negligence toward accepting corporate environmental sustainability. Current literature indicates that awareness and accessibility of information have emerged as major contributory sources behind the most successful climate‐friendly initiatives of people (Fadeeva & Van Berkel, 2021; Gulzari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%